Enhancing the Security of the BB84 Quantum Key Distribution Protocol against Detector-Blinding Attacks via the Use of an Active Quantum Entropy Source in the Receiving Station - Mario Stipčević (Entropy, 2023)
True randomness is necessary for the security of any cryptographic protocol, including quantum key distribution (QKD). In QKD transceivers, randomness is supplied by one or more local, private entropy sources of quantum origin which can be either passive (e.g., a beam splitter) or active (e.g., an electronic quantum random number generator). In order to better understand the role of randomness in QKD, I revisit the well-known “detector blinding” attack on the BB84 QKD protocol, which utilizes strong light to achieve undetectable and complete recovery of the secret key. I present two findings. First, I show that the detector-blinding attack was in fact an attack on the receiver’s local entropy source. Second, based on this insight, I propose a modified receiver station and a statistical criterion which together enable the robust detection of any bright-light attack and thus restore security.